2018
DOI: 10.1007/s00330-018-5414-2
|View full text |Cite|
|
Sign up to set email alerts
|

CT metal artifacts in patients with total hip replacements: for artifact reduction monoenergetic reconstructions and post-processing algorithms are both efficient but not similar

Abstract: • Spectral-detector computed tomography improves assessment of total hip replacements and surrounding tissue. • Virtual monoenergetic images and MAR reduce metal artifacts and enhance image quality. • Evaluation of bone, muscle and pelvic organs can be improved by SDCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
46
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 25 publications
8
46
3
1
Order By: Relevance
“…In line with our results, recent studies reported that combination of VMI and MAR proved to be most effective compared to each method on its own for artifacts from different devices 15,16,22 . A recent phantom study performed with a dual-source dual-energy CT scanner revealed that artifacts caused by coils and clips could also be most effectively reduced using the combination of virtual monoenergetic imaging and dedicated metal artifact reduction algorithms 23 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with our results, recent studies reported that combination of VMI and MAR proved to be most effective compared to each method on its own for artifacts from different devices 15,16,22 . A recent phantom study performed with a dual-source dual-energy CT scanner revealed that artifacts caused by coils and clips could also be most effectively reduced using the combination of virtual monoenergetic imaging and dedicated metal artifact reduction algorithms 23 .…”
Section: Discussionsupporting
confidence: 92%
“…For several implants either VMI and MAR as standalone approaches have been successfully used to reduce artifacts, e.g. total hip replacements, spinal fixation hardware, contrast media, and dental implants 12,13,[22][23][24]27,28 . This aspect is highly relevant as combination of both approaches is only available in dual-energy CT systems which allow for row data-based reconstruction of virtual monoenergetic images (VMI), but clinically used are mainly conventional single-energy CT systems, thereby MAR as a standalone post processing approach has the advantage of a higher availability also in conventional CT systems 12,13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this cohort we were able to show that VNC of TNC can reliably reduce increased liver density due to amiodarone deposition. As frequently applied in comparable studies, we used ROI-based measurements of mean attenuation [22][23][24][25]35 . Still, a volumetric assessment of attenuation covering an entire organ might be less susceptible for any measuring bias.…”
Section: Resultsmentioning
confidence: 99%
“…There is only one detector-based system available, referred to as spectral-detector CT (SDCT). This scanner uses one X-ray source and a detector with two layers; photons with higher energies are detected in the lower layer, while lower energetic photons are detected in the upper layer 21,22 . Material decomposition can be used for the identification of iodine and thereby the creation of virtual non-contrast images (VNC) that offer a way to eliminate the iodine-associated attenuation from images.…”
mentioning
confidence: 99%